Assessing student learning a common sense guide - Suskie, Linda A. (Jossey-Bass, Wiley, 2018)
The third edition adds a stronger emphasis on making assessment useful; greater attention to building a culture in which assessment is used to inform important decisions; an enhanced focus on the many settings of assessment, especially general education and co-curricula; a new emphasis on synthesizing evidence of student learning into an overall picture of an integrated learning experience; new chapters on curriculum design and assessing the hard-to-assess; more thorough information on organizing assessment processes; new frameworks for rubric design and setting standards and targets; and many new resources.